2009
DOI: 10.1080/00207450802324770
|View full text |Cite
|
Sign up to set email alerts
|

Pien Tze Huang, a Composite Chinese Traditional Herbal Extract, Affects Survival of Neuroblastoma Cells

Abstract: Pien Tze Huang is a popular Chinese medicine for liver diseases. In the investigations of possible effects of Pien Tze Huang on the central nervous system, we first studied the in vitro anti-cancer activity of Pien Tze Huang on neuroblastoma cells (SH-SY5Y) as compared with normal fibroblasts (NIH-3T3). Results showed that Pien Tze Huang significantly decreased (p < .05) cell survival of SH-SY5Y as compared to NIH-3T3. Furthermore, the decreases in cell survival of SH-SY5Y were significantly and linearly dose-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 13 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…Besides the inflammation in the CNS, demyelination is also the typical characteristics in MS. Interestingly, several studies have indicated that PZH had a neuroprotective effect [ 40 , 41 ], which makes us speculate whether it also exerts the similar effect in EAE rats. Unfortunately, due to the slight demyelination in an MBP-induced rat model [ 20 ], we did not find marked remyelination in PZH-treated EAE rats (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Besides the inflammation in the CNS, demyelination is also the typical characteristics in MS. Interestingly, several studies have indicated that PZH had a neuroprotective effect [ 40 , 41 ], which makes us speculate whether it also exerts the similar effect in EAE rats. Unfortunately, due to the slight demyelination in an MBP-induced rat model [ 20 ], we did not find marked remyelination in PZH-treated EAE rats (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies found that PZH protected the liver from carbon tetrachloride damage [20] and that PZH showed anti-cancer activities [21]. Our studies on Gingko suggested the possible general molecular mechanisms of neuroprotective effects [6,22,23], including apoptosis, oxidative stress, free radical in the brain cells.…”
Section: Introductionmentioning
confidence: 78%
“…The anti-proliferative activities of PTH in vitro are summarized in Table 1. A previous study showed that PTH can dose-dependently inhibit the survival of neuroblastoma SH-SY5Y cells without affecting normal fibroblast NIH-3T3 cells [54]. PTH also inhibits the viability of human ovarian cancer OVCAR-3 cell line by inducing G1/S-phase cell arrest without inducing apoptosis.…”
Section: Pharmacologymentioning
confidence: 99%